Feeding behavior and metabolic parameters of lambs fed extruded diets in different roughage:concentrate ratios - Oliveira, Karla Alves; Siqueira, Marco Túlio Santos [UNESP]; Ribeiro, Pedro Henrique Cavalcante [UNESP]; Araújo, Laylles Costa; de Andrade, Valdinin Gonçalves; Vilaça, Lucas Eduardo Gonçalves; de Oliveira, Marcela Rodrigues; de Oliveira Faria, Luana; Schultz, Erica Beatriz; de Lima Macedo, Gilberto (Universidade Estadual de Londrina, 2025)
Diets with different proportions of roughage and concentrate influence the feed intake and feeding behavior of ruminants. The use of extruded diets aims to optimize feed efficiency and metabolism, which is essential for improving the productive performance of lambs. The objective was to evaluate the feeding behavior and metabolic parameters of lambs fed different roughage:concentrate ratios on totally extruded diets. Five lambs, 6.0 ± 0.3 months old and weighing 33.3 ± 8.18 kg, were distributed in a Latin square (5 × 5) and fed with different extruded roughage:concentrate (R:C) ratios: 30:70, 40:60, 50:50, 60:40, and 70:30. The dry matter intake and digestibility (1.47 kg day−1 and 67.05%, respectively), water intake (4.71 L day−1), feeding time (169.8 min day−1), rumination time (256.2 min day−1), and metabolic parameters were similar between diets (P≥0.05). The increase in extruded roughage linearly increased the chewing time and linearly reduced idle time (P<0.05). Glucose reached a minimum of 56.4 mg dL−1 at approximately 1:20 pm (P<0.05). A roughage ratio between 30:70 and 70:30 in totally extruded diets did not alter the ingestive, metabolic, or behavioral parameters of sheep. Extruded forage can be increased up to 70% in extruded diets for sheep without compromising the intake or digestibility of the diet’s dry matter.
Comportamento ingestivo e parâmetros metabólicos de cordeiros alimentados com dietas extrusadas em diferentes proporções de volumoso:concentrado
Keywords: Energy; Extrusion; Fiber; Glucose; Rumination